1999
DOI: 10.1055/s-1999-13673
|View full text |Cite
|
Sign up to set email alerts
|

Depth of Insertion At Flexible Sigmoidoscopy: Implications for Colorectal Cancer Screening and Instrument Design

Abstract: Examination of the entire sigmoid was not achieved in approximately one-quarter of patients undergoing screening flexible sigmoidoscopy, mainly because of discomfort. The descending colon is intubated in a minority of cases (using standard instruments), even after 60 cm has been inserted. Alternative instruments with different shaft characteristics (floppy, narrow calibre, 80-100 cm in length) may be necessary to ensure deeper routine intubation in nonsedated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 8 publications
1
50
0
1
Order By: Relevance
“…In the main analysis presented in this article, distal colon was conservatively defined as sigmoid colon or rectum because >50% of flexible sigmoidoscopic examinations reach only the junction of the sigmoid and descending colon (12,13). Ideally, flexible sigmoidoscopy would reach the splenic flexure.…”
Section: Methodsmentioning
confidence: 99%
“…In the main analysis presented in this article, distal colon was conservatively defined as sigmoid colon or rectum because >50% of flexible sigmoidoscopic examinations reach only the junction of the sigmoid and descending colon (12,13). Ideally, flexible sigmoidoscopy would reach the splenic flexure.…”
Section: Methodsmentioning
confidence: 99%
“…FS is not always complete and the descending colon may be intubated in no more than 46% even after 60 cm has been inserted [17,18]. However, the presence of neoplasia within the reach of FS has some predictive value for neoplasia in the right site, whereas the opposite does not seem to be true.…”
Section: Flexible Sigmoidoscopy (Fs)mentioning
confidence: 99%
“…Stewart et al 6 suggest a 25% incomplete examination rate and technical difficulty in up to one third of the cases. Painter et al 7 found that in up to a quarter of the patients, the descending colon was not intubated. Using radiopaque clips, Lehman et al 8 noted that a 60-cm examination reached the splenic flexure in only 33% of patients, a 50-to 55-cm examination reached the sigmoid/ descending colon junction in most instances, a 40- to 45-cm examination the mid to upper sigmoid, and a 30-to 35-cm examination the lower to mid sigmoid.…”
mentioning
confidence: 99%